Adverse childhood experiences, adult trauma, and depressive symptom trajectories. (28th October 2022) - Wilson-Genderson, Maureen; Heid, Allison R.; Cartwright, Francine; Pruchno, Rachel
Abstract: Objectives: Associations among adverse childhood experiences prior to age 18 (ACEs), subjective reports of trauma during Hurricane Sandy, and trajectories of depressive symptoms reported by community-dwelling older people were examined. Methods: We analyzed 6 waves of data from 5, 688 people aged 50–74 recruited in 2006 and followed for 12-years using multilevel mixed effects models. Results: We found that: (1) people who experienced ACEs had trajectories of depressive symptoms in late life that were higher than people not having these experiences, (2) people experiencing two or more ACEs were more likely to report fear and distress when Hurricane Sandy hit than people experiencing either one or no adverse childhood experiences, and (3) while both ACE exposure and peri-traumatic stress were associated with trajectories having higher levels of depressive symptoms, the risk associated with ACEs (especially multiple ACEs) was greater. Conclusion: Findings support life course stress theories including the cumulative inequality theory and stress proliferation theory, suggesting that inequalities are manifested over the life course and that people experiencing adversity during childhood are at increased risk of experiencing adversity in late life. By studying the relationship between adverse childhood experiences and response to Hurricane Sandy our findings demonstrate that adverse childhood experiences can alter the way traumatic events in adulthood are experienced. This finding in turn, has important implications for clinical practice, as it identifies a group of people likely to be at risk for adult trauma.